Republic of Korea : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2012)
The Korean economy is slowing in the face of strong global headwinds. It is projected to bottom out during the course of 2012, regaining momentum towards the end of the year, in line with the global recovery. The main short-term risk to the outlook is a further intensification of the euro area crisis and its spillover. Parliamentary elections took place in April and the presidential election is scheduled for December, making 2012 a year of political transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet